К юбилею Владимира Яковлевича Петрухина - Рашковский, Б.Е. (Хазарский альманах, 2020)
25 июля 2020 года исполняется 70 лет заместителю главного редактора «Хазарского альманаха» Владимиру Яковлевичу Петрухину. Юбиляр – историк, археолог, известнейший и авторитетнейший специалист в области истории и культуры средневековой Восточной Европы, не нуждается в специальном представлении на страницах нашего альманаха: В. Я. Петрухин работает в составе редколлегии альманаха с момента его создания в 2002 г. This article is dedicated to the 70th Birthday of Deputy Chief Editor of “Khazar Almanac” – Vladimir Petrukhin, the famous researcher of the Ancient Rus’ and the Khazar khaganate. Studying the Early Medieval history of Eastern Europe, V. Petrukhin he stood fi rm in anti-panslavistic positions. He assigned a leading role not only to the Slavs, but also to the Scandinavians and the Turks. The Khazars were among of them. V. Petrukhin is author of many publications on these areas of research.